KEBIJAKAN HUKUM KESEHATAN ATAS KIA-KB UNTUK MASYARAKAT INDONESIA - Hutajulu, Maria Margaeta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The acceptance of KIA-KB policy information is that the community's right to obtain clear, accurate, and easily accessible information is an integral part of the right to health. Accurate information encourages active participation in the KIA-KB program and increases awareness of available service options. However, obstacles such as low health literacy, inequality in access to information, and lack of effective socialization from the government are still obstacles. Therefore, the state through Law No. 17 of 2023 and the BPJS Law is required to ensure that the health information system runs inclusively, transparently, and fairly for the entire community. The method of distributing costs, tools, or medicines in the KIA-KB program emphasizes the importance of implementing ethical health principles such as justice, usefulness, and non-discrimination. Unfair distribution can lead to inequality in services, endanger vulnerable groups, and violate the right to health. Therefore, distribution must be based on needs, transparent, and accountable, in accordance with the mandate of Law No. 17 of 2023 concerning Health and Law No. 24 of 2011 concerning BPJS. This ethical approach is important so that KIA-KB services can be felt evenly and sustainably by all levels of society.Keywords: Legal Policy, Health, KIA-KB, Society